Noncovalent Bonds, Spectral and Thermal Properties of Substituted Thiazolo[2,3-b][1,3]thiazinium Triiodides - Irina Yushina (Crystals, 2019)
The interrelation between noncovalent bonds and physicochemical properties is in the spotlight due to the practical aspects in the field of crystalline material design. Such study requires a number of similar substances in order to reveal the effect of structural features on observed properties. For this reason, we analyzed a series of three substituted thiazolo[2,3-b][1,3]thiazinium triiodides synthesized by an iodocyclization reaction. They have been characterized with the use of X-ray diffraction, Raman spectroscopy, and thermal analysis. Various types of noncovalent interactions have been considered, and an S…I chalcogen bond type has been confirmed using the electronic criterion based on the calculated electron density and electrostatic potential. The involvement of triiodide anions in the I…I halogen and S…I chalcogen bonding is reflected in the Raman spectroscopic properties of the I−I bonds: identical bond lengths demonstrate different wave numbers of symmetric triiodide vibration and different values of electron density at bond critical points. Chalcogen and halogen bonds formed by the terminal iodine atom of triiodide anion and numerous cation…cation pairwise interactions can serve as one of the reasons for increased thermal stability and retention of iodine in the melt under heating.